Cellular oxidative stress response mediates radiosensitivity in Fus1-deficient mice - Yazlovitskaya, E M (Cell Death Dis, 2015)
Mechanism of radiosensitivity of normal tissues, a key factor in determining the toxic side effects of cancer radiotherapy, is not fully understood. We recently demonstrated that deficiency of mitochondrial tumor suppressor, Fus1, increases radiosensitivity at the organismal, tissue and cellular levels. Since Fus1-deficient mice and cells exhibit high levels of oxidative stress, we hypothesized that dysregulation of cellular antioxidant defenses may contribute to the increased radiosensitivity. To address this potential mechanism, we treated the Fus1 KO mice with an inhibitor of pathogenic oxidative reactions, pyridoxamine (PM). Treatment with PM ameliorated IR-induced damage to GI epithelium of Fus1 KO mice and significantly increased the survival of irradiated mice. In cultured Fus1 KO epithelial cells, IR-induced oxidative stress was enhanced because of inadequate cellular antioxidant defenses, such as low levels and/or activities of cytochrome C, Sod 2 and STAT3. This resulted in dysregulation of IR-induced DNA-damage response and DNA synthesis. Treatment of Fus1 KO cells with PM or Sod 2 mimetic Tempol normalized the oxidative stress response, thus compensating to a significant degree for inadequate antioxidant response. Our findings using Fus1 KO radiosensitive mice suggest that radiosensitivity is mediated via dysregulation of antioxidant response and defective redox homeostasis.